2017
DOI: 10.1021/acs.joc.7b02573
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting C- and O-Atom Reactivities of Neutral Ketone and Enolate Forms of 3-Sulfonyloxyimino-2-methyl-1-phenyl-1-butanones

Abstract: The mechanisms of intramolecular cyclization of 3-sulfonyloxyimino-2-methyl-1-phenyl-1-butanones (1) under basic (DABCO and t-BuOK) and acidic (AcOH and TFA) conditions were investigated by means of experimental and computational methods. The ketone, enol, and enolate forms of 1 can afford different intramolecular cyclization products (2, 3, 4), depending on the conditions. The results of the reaction of 1 under basic conditions suggest intermediacy of neutral enol (DABCO) and anionic enolate (t-BuOK), while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 130 publications
0
10
0
Order By: Relevance
“…The reaction proceeded smoothly as indicated by TLC results and furnished two products, which were characterized as isomeric isoxazoles 3s and 5s on the basis of their spectral and analytical data (Scheme ). Obviously, 3s and 5s were formed through chemoselective rearrangement of 2 H -azirine 4s , , and the selectivity might be attributed to the different reactivity of O -atom in a ketone or an amide group . This finding provided an alternative protocol for the synthesis of fully substituted isoxazoles of type 3 and 5 .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The reaction proceeded smoothly as indicated by TLC results and furnished two products, which were characterized as isomeric isoxazoles 3s and 5s on the basis of their spectral and analytical data (Scheme ). Obviously, 3s and 5s were formed through chemoselective rearrangement of 2 H -azirine 4s , , and the selectivity might be attributed to the different reactivity of O -atom in a ketone or an amide group . This finding provided an alternative protocol for the synthesis of fully substituted isoxazoles of type 3 and 5 .…”
Section: Resultsmentioning
confidence: 86%
“…21 Obviously, 3s and 5s were formed through chemoselective rearrangement of 2H-azirine 4s, 25,26 and the selectivity might be attributed to the different reactivity of O-atom in a ketone or an amide group. 27 This finding provided an alternative protocol for the synthesis of fully substituted isoxazoles of type 3 and 5.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The intramolecular cyclization process of 2‐methyl‐1‐phenyl‐3‐(sulfonyloxyimino)butan‐1‐ones under alkaline and acidic conditions were established, and the mechanical characteristics were studied by Ohwada et al They found that the reaction of the 2‐alkyl‐1‐phenyl‐3‐(sulfonyloxyimino)butan‐1‐one system under alkaline conditions (DABCO) resulted in the formation of neutral enols, which resulted 2 H ‐azirines (Scheme 17) [33].…”
Section: Neber Rearrangementmentioning
confidence: 99%
“…Alarmingly, however, such an approach is more complicated when one considers that both the oxazole and isoxazole can be prepared from the same starting ketoxime (9, Scheme 1). 29 The 14 N-filtered 13 C NMR spectra of oxazole (10) and isoxazole (11) enable the straightforward differentiation of the heterocyclic isomers (Figure 3E,F). 10 displays two 13 C NMR signals with C−N bonds, while 11 only exhibits one 13 C NMR signal with a C−N bond.…”
mentioning
confidence: 99%